Asset Forfeiture (In Rem): Economic Crime and Asset Confiscation Bill - Halimatu Hira, Rr. (LPPM Universitas Lampung, 2022)
The rampant economic crimes at this time are crucial aspects of the nation's life. It is because factually and potentially the form of financial crime causes losses to the economy of a country. Indications of criminal cases in the economic field are also increasingly difficult to eradicate because the modus operandi is more complicated and takes a long time, especially related to the return of lost state assets. Therefore, the idea of a draft law on assets confiscation resulting from criminal acts emerged. This legal product is considered to be a solid set of regulations in seizing the assets of economic crimes through more comprehensive procedures or procedures. Thus, through this article, we will discuss in more depth in terms of the history, objectives, and substance of the draft asset confiscation law. In addition, the research method to be used is the normative juridical method sourced from both primary and secondary data sources. So, in its output, the urgency of this bill can be proven both in terms of asset recovery to steps or strategies to recover state losses that have been caused. Thus, economic crimes in Indonesia will be completely eradicated.